Analysis of User Satisfaction Level on Halodoc Application in Jakarta - Charunia; Febrilia, Ika; Aditya, Shandy (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Halodoc is the number one health application in Indonesia in demand by the public. This study aims to determine the level of satisfaction of Halodoc users in Jakarta. The sample and population in this study were 105 Halodoc users domiciled in Jakarta using a purposive sampling method and data collection through distributing questionnaires conducted online via Google Forms. This study uses validity tests and reliability tests as instrument tests. This study uses four data analysis methods, namely descriptive analysis, t-test, mean test,and standard deviation test used to process data through SPSS 29 software. The results of this study indicate that there are three dimensions to determine the level of satisfaction of Halodoc users in Jakarta. The three dimensions are ease of use and satisfaction, system information arrangement, and system usefulness. The results of this study indicate that no statistically significant differences in opinion were observed about all dimensions. This research is expected to be used by companies as a basis for Halodoc user satisfaction surveys and to improve and provide user convenience.